Digital Heritage: Progress in Cultural Heritage. Documentation, Preservation, and Protection (EuroMed 2020) - (:unkn) unknown (My University, 2021)
This book constitutes the refereed post-conference proceedings of the 8th International Conference on Digital Heritage, EuroMed 2020, held virtually in November 2020. The 37 revised project papers and 30 revised short papers presented were carefully reviewed and selected from 326 submissions. The papers are on topics such as digital data acquisition technologies in CH/2D and 3D data capture methodologies and data processing; remote sensing for archaeology and cultural heritage management and monitoring; interactive environments and applications; reproduction techniques and rapid prototyping in CH; e-Libraries and e-Archives in cultural heritage; virtual museum applications (e-Museums and e-Exhibitions); visualisation techniques (desktop, virtual and augmented reality); storytelling and authoring tools; tools for education; 2D and 3D GIS in cultural heritage; and on-site and remotely sensed data collection.
Keywords: 3D imaging; 3D modeling; Artificial intelligence; Cultural heritage; Digital preservation; Digitization; GIS; Image processing